Beyond representation philosophy and poetic imagination - Eldridge, Richard Thomas 1953- (Cambridge studies in philosophy and the arts, 1996)
The essays in this 1996 volume explore the ways in which traditional philosophical problems about self-knowledge, self-identity, and value have migrated into literature since the Romantic and Idealist periods. How do so-called literary works take up these problems in a new way? What conception of the subject is involved in this literary practice? How are the lines of demarcation between philosophy and literature problematised? The contributors examine these issues with reference both to Romantic and Idealist writers and to some of their literary and philosophical inheritors and revisers. Their essays offer a philosophical understanding of the roots and nature of contemporary literary and philosophical practice, and elaborate, powerful and influential, but rarely decisively articulated, conceptions of the human subject and of value